2021
DOI: 10.1111/liv.14906
|View full text |Cite
|
Sign up to set email alerts
|

A nonbile acid farnesoid X receptor agonist tropifexor potently inhibits cholestatic liver injury and fibrosis by modulating the gut–liver axis

Abstract: Background & Aims Tropifexor (TXR) is a novel nonbile acid that acts as an agonist of farnesoid X receptor (FXR). TXR is currently in Phase 2 trials for the treatment of non‐alcoholic steatohepatitis (NASH). Herein, we report the impact of TXR on in a piglet model in which cholestatic liver damage and fibrosis where induced by bile duct ligation (BDL). Methods The piglets received BDL and TXR for 2 wk. Hepatic, portal and colonic bile acid and amino acid profiles and gut microbiome were analysed. Portal fibrob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 50 publications
(106 reference statements)
4
24
0
Order By: Relevance
“…One explanation for this may be related to the reported antagonistic effects of HCA species on FXR activation (Zheng et al, 2021) which could account for reduced secretion of FGF-19 from hepatocytes and low levels of circulating FGF-19 in BDL piglets (Johansson et al, 2020;Song et al, 2009). Targeting this pathway has recently shown promising results for prevention of liver pathology in cholestatic piglets, although the translatability to humans and implications for brain function have yet to be determined (Xiao et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…One explanation for this may be related to the reported antagonistic effects of HCA species on FXR activation (Zheng et al, 2021) which could account for reduced secretion of FGF-19 from hepatocytes and low levels of circulating FGF-19 in BDL piglets (Johansson et al, 2020;Song et al, 2009). Targeting this pathway has recently shown promising results for prevention of liver pathology in cholestatic piglets, although the translatability to humans and implications for brain function have yet to be determined (Xiao et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“… 141 A recent study in piglets subjected to BDL confirmed the beneficial effects of the FXR agonist tropifexor on intestinal inflammation and the gut barrier and indicated significant changes of the microbiome. 142 …”
Section: Intestinal Barrier and Bacterial Translocationmentioning
confidence: 99%
“…Immunofluorescence was performed using the chromogen diaminobenzidine as described previously. 18 Briefly, the slides were hydrated and blocked with 5% bovine serum albumin in PBS. The antibodies of cholesterol 7α-hydroxylase (CYP7A1) (Millipore, dilution, 1:100) were applied in a wet chamber overnight at 4°C.…”
Section: Immunofluorescencementioning
confidence: 99%
“…The composition of bile acids (BAs) in the livers, serum, and colonic contents was measured according to the previously described method. [18][19][20] The BA quantification was performed using the Waters Xevo TQ-S mass spectrometer coupled to the Waters ACQUITY ultraperformance liquid chromatography system.…”
Section: Bile Acid Measurementmentioning
confidence: 99%
See 1 more Smart Citation